Sympatric and allopatric Alcolapia soda lake cichlid species show similar levels of assortative mating - Lawson, Michael R. M.; Hayle, Michael G. B.; Shechonge, Asilatu H.; Nyingi, Wanja Dorothy; Ford, Antonia G. P.; Hoffman, Joseph I.; Day, Julia J.; Turner, George F.; Dasmahapatra, Kanchon K. (Frontiers in Ecology and Evolution, 2023)
Characterising reproductive barriers such as mating preferences within rapid evolutionary radiations is crucial for understanding the early stages of speciation. Cichlid fishes are well-known for their adaptive radiations and capacity for rapid speciation and as such we investigate assortative mating among Alcolapia species; a recent (<10,000 years), small adaptive radiation, endemic to the extreme soda lakes, Magadi (one species) and Natron (three species), in East Africa. In seminatural aquarium conditions, we observed both courtship and mate choice (tested by microsatellite paternity analysis) to be significantly assortative among the three sympatric Natron species in a three-way choice experiment. This was also the case between allopatric species from Natron and Magadi, as found in a two-way choice experiment. However, the proportion of disassortative matings was substantial in both of these experiments, with hybrids comprising 29% of offspring in sympatric species and 11.4% in allopatric species comparisons. . Previous work suggests that the Natron/Magadi split might not be much older than the radiation within Natron, so the similar rate of hybridisation in the allopatric comparison is surprising and inconsistent with predictions of reinforcement theory, which predicts a faster rate of accumulation of premating isolation in sympatry. The relatively weak assortative mating in sympatry suggests that additional reproductive barriers, such as microhabitat preferences or spatial structuring may contribute to genetic isolation in nature.